2011
DOI: 10.1111/j.1469-0691.2010.03347.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of the smooth tubercle bacilli ‘Mycobacterium canettii’ infection suggest the existence of an environmental reservoir

Abstract: Over a 3-year follow-up, 30 out of the 318 unique Mycobacterium tuberculosis complex isolates recovered in the Republic of Djibouti had a smooth-type morphology and were Niacine-negative, the characteristics of 'Mycobacterium canettii' strains. Unlike M. tuberculosis, 'M. canettii' grew on nutrient-poor media at 30°C, and possessed characteristic lipids. They were isolated from respiratory and extra-respiratory sites from patients with typical forms of tuberculosis. Most cases resolved with antibiotic therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(96 citation statements)
references
References 16 publications
1
89
0
6
Order By: Relevance
“…M. canettii strains are remarkable, rare mycobacteria, which are almost exclusively isolated from patients in the region of the Horn of Africa (35, 36). Their mode of transmission seems to be different to M. tuberculosis because no human-to-human transmission of M. canettii strains was yet reported (18,35,37). M. canettii strains might have a yet-unknown, possibly aquatic, environmental reservoir where different strains can get in frequent direct contact, thereby enhancing the possibilities of HGT (10,17,38,39).…”
Section: Discussionmentioning
confidence: 99%
“…M. canettii strains are remarkable, rare mycobacteria, which are almost exclusively isolated from patients in the region of the Horn of Africa (35, 36). Their mode of transmission seems to be different to M. tuberculosis because no human-to-human transmission of M. canettii strains was yet reported (18,35,37). M. canettii strains might have a yet-unknown, possibly aquatic, environmental reservoir where different strains can get in frequent direct contact, thereby enhancing the possibilities of HGT (10,17,38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Every MTC species has a limited range of natural hosts, but there is no specific barrier and any MTC species can potentially infect any susceptible host species (Djelouadji et al, 2011). Humans are infected worldwide by sympatric M. tuberculosis sensu stricto families (Gagneux et al, 2006), whereas patients who are exposed in Africa may also be infected by Mycobacterium africanum (de Jong et al, 2010) and Mycobacterium canettii (Koeck et al, 2011;Van Soolingen et al, 1997). Zoonotic tuberculosis can be due to Mycobacterium caprae, Mycobacterium microti (Panteix et al, 2010) or the bovine tuberculosis agent Mycobacterium bovis (Thoen & LoBue, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A detailed study has shown that the unusual smooth morphology "M. canettii" strains appear to form a pivotal role in the evolution of tuberculosis [84]. Although extant strains of "M. canettii" still cause human tuberculosis, they differ significantly in infectivity and appear to be relatively ancestral [85,86]. Genomic studies indicate that the very diverse "M. canettii" isolates appear to coalesce into a form of bottleneck after which all the modern human and animal biotypes evolved in a relatively linear manner [83,84,87,88].…”
Section: Evolutionary and Pathogenicity Aspects Of Cell Envelope Compmentioning
confidence: 99%
“…However, some most significant new lipid structural principles are introduced in "M. canettii" (Figure 11). Two major classes of acyl trehalose glycolipids, the DATs and PATs (Figure 5), are encountered [86]. The relatively polar DATs are good antigens, which probably contribute to the cell surface properties of tubercle bacilli [38].…”
Section: Evolutionary and Pathogenicity Aspects Of Cell Envelope Compmentioning
confidence: 99%